Prescriptions for manners in English courtesy literature, 1690-1760, and their social implications - Childs, F (1984)
The thesis is an examination of the courtesy literature written and/or published in England between 1690 and 1760. Its purpose is to find out about theories of manners in this period and to explore their social implications. Chapter 1 establishes the context and parameters of the study; defines 'courtesy literature', and presents information about its degree of influence in eighteenth-century England. Chapter 2 surveys the distinguished historical tradition of writings on manners which preceded this period, and examines the influence of these earlier works on English theorists. Chapter 3 describes the eighteenth-century English concept of good breeding and reveals its close relationship to contemporary aesthetic ideals. Chapter 4 is a detailed examination of prescriptions of manners for the gentleman. It describes how the gentleman's manners were intended to operate as a major means of reinforcing his social rank. It explores the social implications of this ideal, and argues in particular that it acted to reinforce the cultural and social hegemony of the ruling elite. Chapter 5 outlines the prescriptionsofmanners for ladies in this period in terms of both their rank and their sex, and stresses that, of these two determinants, the latter was at least as important as the former. Chapter 6 looks at prescriptions for servants and apprentices in a continued exploration of these two themes of rank and sex. It discovers a significant extension downwards of the gentlemanly ideal to aspiring tradesmen. Chapter 7 concludes the thesis with an assessment of its major discoveries, and argues that the study of these cultural norms is a valuable means of gaining a better understanding of eighteenth-century people's perceptions of themselves and their society.